ENVIRONMENTAL SCANNING AND PERFORMANCE IN SMALL FIRMS (INMR - Innovation & Management Review, 2011)
Environmental scanning is the process of searching for information in the external environment. Its importance to the study of strategy lies in the fact that it constitutes the first link in the chain of perceptions and actions that allows an organization to adapt to its environment, and can influence it, therefore, in achieving superior performance. This study aims at analyzing the relationship between environmental monitoring practices and performance in small businesses. The research was carried out in ninety-two companies, with the application of questionnaires with closed questions, directed to the main manager or the establishment owner. For the associations between monitoring practices and characteristics of size, age, and performance, we calculated the correction coefficient. In order to test the relationship between monitoring and performance, the sample was ordered according to performance levels and divided in three groups – high, medium, and low performance enterprises – an Analysis of Variance – ANOVA. The results corroborated partially the studies that confirmed a positive relation between monitoring practices and development in small companies. The frequency of monitoring of environment aspects, as well as the frequency of access to information sources, indicated results associated with some of the development measures.